Provisionamento de processos judiciais e administrativos: análise crítica e propostas de boas práticas - Kietzmann, Luís Felipe de Freitas (2016)
This paper focuses on Brazilian standards concerning the provision and the disclosure of contingent liabilities specifically aiming at their use in legal and managerial proceedings, which are the kind of contingent liability that most significantly impacts the results of the majority of national companies in all segments. The description of the standards, therefore, is compared to the market reality and the specifications pertaining to legal and managerial proceedings. In addition to contextualizing the applicable rules and explaining how they work, in special Technical Standard number 25, created by the Committee of Accounting Standards, which became mandatory for publicly-held corporations by CVM Decision number 594, as of September 15, 2009, their critical analysis is also performed, with the identification of any omissions that might make it difficult to perform the provision activities by the appropriate professionals, which leads to a lack of uniformity of these records in the company's financial statements, as well as making it possible to manage results. Next, solutions are assessed and proposed for the problems found, in special the adoption of percentage values for risk classification criteria and the definition of contingency value measurement and contingent liability mensuration criteria organized as standards of good practices of provision and disclosure of contingent liabilities arising from legal and managerial proceedings.